Reinvestigate how education and work experience determine work ethic of employee - Muhammad Syafii A Basalamah (Institute of Computer Science (IOCS), 2023)
The research described is a quantitative study conducted at companies engaged in financing at the XYZ Finance branch office in Makassar City. The study aimed to investigate how education and work experience support the work ethic of employees in the financial sector, where work demands, workload, and stress are high. Education and work experience were used as independent variables, while work ethic was the dependent variable. A total of 61 respondents were selected through a simple random sampling technique, and data was collected using a questionnaire technique. The results of the study showed that work experience had a positive and partially significant effect on work ethic, while education had a partial and insignificant effect on work ethic. This finding is consistent with the idea that more experience in a particular field can lead to a better work ethic. However, it is important to note that the significance of education than work experience can vary depending on the specific field and industry. To ensure the validity and reliability of the study's results, the researchers conducted validity and reliability tests, as well as classical assumption tests in the form of normality, multicollinearity, and heteroscedasticity tests. Additionally, this research used multiple regression tests, t-tests, and the coefficient of determination to analyze the data. Overall, this research highlights the importance of work experience in developing a strong work ethic, particularly in high-stress industries such as the financial sector. However, it is also important to continue to prioritize education and training to ensure that employees have the necessary knowledge and skills to succeed in their career.